Efeito inibitório, in vitro, do iodeto de potássio e da miltefosina frente a cepas do complexo Sporothrix schenckii em biofilme nas formas filamentosa e leveduriforme - Silva, Maria Lucilene Queiroz da (2017)
The most infections are caused by microorganisms associated with biofilms and it has been recently demonstrated that dimorphic fungus, belonging the etiological agent of Sporotrichosis Sporothrix schenkii complex, is also able to form biofilm. Microorganisms when associated in biofilms may develop resistance to antibiotic therapy. The objective of this study was to evaluate the ability of S. schenckii complex yeasts to form biofilm, in vitro, as well as characterize the growth kinetics and susceptibility of filamentous and yeast biofilms to potassium iodode (KI) and miltefosine (MIL). Eighteen strains of S. schenckii complex (10 S. brasiliensis, 4 S. mexicana, 2 S. globosa and 2 S. schenckii sensu stricto) were used. For the formation of yeast biofilms, inoculums at the concentration of approximately 1 x 106 CFU / mL were used in 0.9% saline solution and maturation was done in RPMI medium. For the growth kinetics and sensitivity of biofilms, the techniques of metabolic activity and biomass evaluation were performed. For the planktonic sensitivity, the broth dilution technique was used, according to the CLSI methodologies. And for the biofilm morphology were evaluated by optical microscopy, SEM and confoval.The maturation time of yeast biofilms was, in average, 96 h. Results showed that KI and MIL had an inhibitory effect against all strains, in planktonic form (filamentous and yeast phases). The MICvalues ranged from 62.5 to 250 mg/mL for KI and from 0.125 to 4 μg/mL for MIL. Afterward, drugs were tested against mature biofilms of Sporothrix spp., at following concentrations: MIC, 10 x MIC and 50 x MIC.The metabolic activity and biomass of filamentous biofilms was inhibited by KI (10 x MIC) with a meanof 75.4%and MIL (50xMIC) inhibited, on average, 55.1%. For biofilms in yeast phase, the mean inhibition for KI (10 x MIC) and MIL (50 x MIC) was 67.7% and 51.6%, respectively. This study demonstrated that strains of various species of S. schenckii complex in yeast phase are able to form biofilm in vitro, and that potassium iodide and miltefosine have an inhibitory effect against filamentous and yeast biofilms.